Causes of Death in the 12 Months After Hospital Discharge Among Patients With Opioid Use Disorder. Issue 4 (10th July 2022) - King, Caroline; Cook, Ryan; Korthuis, P. Todd; Morris, Cynthia D.; Englander, Honora
Abstract : Background: Patients with substance use disorders are seven times more likely hospitalized than the general population. However, causes of death for recently hospitalized patients with Opioid Use Disorder (OUD) are not well described. This study describes causes of death in the year post-discharge among hospitalized patients with OUD. Methods: We analyzed data from participants who were at least 18 years old, with Medicaid insurance, and had a diagnosis of OUD during a general hospital admission in Oregon between April 2015 and December 2017. Results: During the study window, 6, 654 Oregon Medicaid patients with an OUD diagnosis were hospitalized. Patients were predominately female (56.7%) and White (72.2%), an average age of 44.2 years (SD = 15.4 years) and average hospital length of stay of 6.5 days (SD = 10.9 days). In the 12 months post-discharge, 522 patients died (7.8%); 301 patients from a drug or substance related cause (4.5%), including 71 from drug overdose (1.1%). Stated another way, of those who died within 12 months, 58% of deaths were attributed to drug-related causes, including 13.6% of deaths attributed to overdose; 42% died of non-drug related causes. Drug-related death was the most frequent cause of mortality. Conclusions: Hospitalized patients with OUD are at high risk of death, from drug and non-drug related causes, in the year after discharge. Future research should consider not only overdose, but a more comprehensive definition of drug-related death in understanding post-discharge mortality among hospitalized patients with OUD, and care systems should work to mitigate the risk of death in this population.